Pleural chondroid metaplasia in a background of IgG4 plasma cell rich chronic inflammatory infiltrate: report of a rare case with review of literature - Spinelli, M.; Datta, A.; Montero Fenandez, M.A.; Viola, P. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
Mesothelial reactive and degenerative changes secondary to inflammatory conditions, toxin exposure, neoplastic and non-neoplastic disease are often encountered in routine histopathology practice. Herein, we report a very rare case of pleural chronic inflammation with features suggestive for IgG4-related disease associated with the formation of a nest of mature, benign looking cartilage in the pleura of a middle age male patient. The review of the pertinent literature reveals that to date, only few cases of chondroid metaplasia or benign tumor (choristoma) are reported in mesothelium and only occasionally in this change is found in the pleura.